Overdose and take‐home naloxone in emergency settings: A pilot study examining feasibility of delivering brief interventions addressing overdose prevention with 'take‐home naloxone' in emergency departments. (12th January 2022) - Black, Eleanor; Monds, Lauren A; Chan, Betty; Brett, Jonathan; Hutton, Jennie E; Acheson, Liam; Penm, Jonathan; Harding, Sally; Strumpman, Dana; Demirkol, Apo; Lintzeris, Nicholas
Abstract: Objective: Although most unintentional opioid deaths in Australia are attributed to pharmaceutical opioids, take‐home naloxone (THN) programmes have to date predominantly targeted people using illicit opioids in drug treatment and harm reduction settings. We sought to examine the feasibility of delivering THN brief interventions (THN‐BIs) with intranasal naloxone in EDs. Methods: This pilot feasibility study was conducted across three major metropolitan EDs in Sydney and Melbourne. ED staff were surveyed about their perspectives regarding THN before completing a 30‐min training programme in THN‐BI delivery. Patients presenting with opioid overdose or considered high risk for future overdose were eligible to receive the THN‐BI. Staff survey responses were compared between hospitals and provider types using one‐way analysis of variances. Patient demographic and clinical characteristics were extracted from medical records and compared between hospitals and overdose type using Fisher's exact test and one‐way analysis of variances. Results: One hundred and twenty‐two ED staff completed the survey. One hundred and ten (90.2%) agreed that EDs should provide THN‐BIs, whereas 23 (19.2%) identified time constraints and 17 (12.9%) felt uncomfortable discussing overdose with patients. Fifty‐seven patients received the THN‐BI, with the majority ( n  = 50, 87.7%) having presented following opioid overdose. The median age was 44 years and 40 (71.4%) were men. Two‐thirds of the overdoses ( n  = 31, 66.0%) were attributed to heroin with one‐third ( n  = 16, 34%) being attributed to pharmaceutical opioids. Conclusions: ED‐based delivery of THN‐BIs can reach a wide range of individuals at‐risk of overdose. The present study supports the feasibility of THN interventions in EDs and underscores the importance of addressing implementation barriers including staff training. Abstract : Most unintentional opioid deaths in Australia are attributed to pharmaceutical opioids, but take‐home naloxone (THN) programmes have to date predominantly targeted people using illicit opioids in drug treatment and harm‐reduction settings. This pilot study examined whether it was feasible to deliver a THN brief intervention (THN‐BI) to people at risk of opioid overdose in three EDs in New South Wales and Victoria. There were 122 ED staff who participated with most ( n  = 110, 90.2%) agreeing that EDs should provide THN‐BIs, and there were 57 patients who received the THN‐BI, with the majority ( n  = 50, 87.7%) having presented following opioid overdose.